Piranti kohesi dalam Kinderroman Emil und die Detektive karya Erich Kästner dan padanannya dalam bahasa Indonesia - Oktavia, Rindi; Widodo, Pratomo (Universitas Negeri Yogyakarta, 2025)
The focus of this research aims to describe 1) the types of German cohesion devices and 2) the equivalent types of cohesion devices in Indonesian used in the Kinderroman Emil und die Detektive by Erich Kästner which was first published in 1929. This study is a qualitative research with the subject of the Kinderroman Emil und die Detektive by Erich Kästner and its translation entitled Emil and the Secret Police. The object of this research is all cohesion devices contained in the sentences of Kinderroman Emil und die Detektive and their equivalents in Indonesian. Data collection uses the listening method with the basic technique of tapping and the advanced technique of note-taking. Agih method, referential pairing method, and translational pairing method are the methods used for data analysis. Data validity was tested through intrarater and expert judgment. The results of this study are as follows. 1) There are 2131 cohesion devices used in Kinderroman Emil und die Detektive consisting of 56 repetitions, 379 coordinative conjunctions, 81 subordinative conjunctions, 66 substitutions, 909 forms of reference, 342 articles, 199 omissions, and 99 deixis. 2) A total of 1593 equivalent types of cohesion devices in Indonesian consisting of 847 references, 56 substitutions, 199 ellipses, 350 coordinative conjunctions, 69 subordinative conjunctions, and 72 reiterations.